2007
DOI: 10.1002/aoc.1323
|View full text |Cite
|
Sign up to set email alerts
|

Vinyl polymerization of norbornene by nickel(II) complexes bearing β‐diketiminate ligands

Abstract: Norbornene polymerizations were carried out using nickel(II) bromide complexes CH{C(R)NAr} 2 NiBr (1, R = CH 3 , Ar = 2, 6− i Pr 2 C 6 H 3 ; 2, R = CH 3 , Ar = 2, 6-Me 2 C 6 H 3 ; 3, R = CF 3 , Ar = 2, 6− i Pr 2 C 6 H 3 ; 4, R = CF 3 , Ar = 2, 6-Me 2 C 6 H 3 ) in the presence of methylaluminoxane. Compound 3 is the most active norbornene polymerization catalyst of all the nickel complexes tested. The activity of theses catalysts increases with increases in steric bulk of the substituents on the aryl rings. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…The optimal Al/Ni ratio was shown to be 1500. Variation of the polymerization temperatures from 0 • C to 90 • C caused a steady increase in the activities, whereas the molecular weights of the PNB decreased at the same time [137].…”
Section: Nn-chelate and Bis(n) Ligandsmentioning
confidence: 93%
“…The optimal Al/Ni ratio was shown to be 1500. Variation of the polymerization temperatures from 0 • C to 90 • C caused a steady increase in the activities, whereas the molecular weights of the PNB decreased at the same time [137].…”
Section: Nn-chelate and Bis(n) Ligandsmentioning
confidence: 93%
“…The vinylic polymerization of norbornene with Pd(II) catalysts was patented in 1967, and much research has been done with different metal catalysts (Ni(II), Pd(II), Cr(III), Co(II), Cu(II)) [42][43][44][45][46]. In 1989, Kaminsky developed a process of synthesis using metallocene catalysts, in particular zirconocene and half-sandwich titanium methylaluminoxane (MAO) catalysts [47][48][49][50], allowing the development of a perfectly transparent material with a great rigidity, which was in the centre of several research efforts [35,[51][52][53][54][55][56][57][58][59][60].…”
Section: Cyclic Olefin Copolymers (Coc) Development Of Cyclic Olefin mentioning
confidence: 99%
“…[19] The 1 H and 13 C NMR spectra are very similar to those reported and also show no resonances assignable to double bonds. [11,18] The SEC measurements of several samples indicated that high-molecular weight polymers with a rather low polydispersity are formed. Unfortunately, a large number of polynorbornene samples could not be analyzed by size exclusion chromatography; due to the high molecular weight these polymers could not be dissolved in the commonly used chlorobenzene or 1,3,5-trichlorobenzene, even after stirring at elevated temperatures for several days.…”
Section: Catalytic Studiesmentioning
confidence: 99%
“…[11] A reaction between the catalyst precursor and MAO in the presence of norbornene yields a nickel compound with a methyl ligand and a coordinated norbornene (A). The norbornene then inserts into the Ni-CH 3 bond to give the coordinatively unsaturated species B.…”
Section: Mechanistic Considerationsmentioning
confidence: 99%
See 1 more Smart Citation